Glycolytic switch in response to betulinic acid in non-cancer cells. - Elke H Heiss; Matthias P Kramer; Atanas G Atanasov; Hortenzia Beres; Daniel Schachner; Verena M Dirsch (PLoS ONE)
The naturally occurring triterpenoid betulinic acid (BA) shows pronounced polypharmacology ranging from anti-inflammatory to anti-lipogenic activities. Recent evidence suggests that rather diverse cellular signaling events may be attributed to the same common upstream switch in cellular metabolism. In this study we therefore examined the metabolic changes induced by BA (10 µM) administration, with focus on cellular glucose metabolism. We demonstrate that BA elevates the rates of cellular glucose uptake and aerobic glycolysis in mouse embryonic fibroblasts with concomitant reduction of glucose oxidation. Without eliciting signs of obvious cell death BA leads to compromised mitochondrial function, increased expression of mitochondrial uncoupling proteins (UCP) 1 and 2, and liver kinase B1 (LKB1)-dependent activation AMP-activated protein kinase. AMPK activation accounts for the increased glucose uptake and glycolysis which in turn are indispensable for cell viability upon BA treatment. Overall, we show for the first time a significant impact of BA on cellular bioenergetics which may be a central mediator of the pleiotropic actions of BA.